Social Desirability and Its Effect on Help-Seeking: Mediated by Shame - Lee, Angel; Iskandar, Amirul (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study aimed to investigate the relationship between social desirability and help-seeking behavior, with shame as a mediating variable, among a sample of Malaysian participants.Methods and Materials: This research employed a descriptive correlational design and was conducted on a sample of 391 participants from Malaysia, selected based on the Morgan and Krejcie sample size table. Standardized instruments were used to assess help-seeking (General Help-Seeking Questionnaire), social desirability (Marlowe-Crowne Social Desirability Scale), and shame (Experience of Shame Scale). Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation analysis, and AMOS-21 was employed to conduct Structural Equation Modeling (SEM) to test the hypothesized mediation model and assess the model fit using key indices such as CFI, RMSEA, and TLI.Findings: Descriptive analysis revealed moderate levels of help-seeking (M = 4.62, SD = 1.13), high social desirability (M = 21.87, SD = 4.76), and elevated shame (M = 68.34, SD = 9.51). Pearson correlation analysis showed that social desirability was negatively correlated with help-seeking (r = −.41, p < .001) and positively with shame (r = .46, p < .001), while shame was negatively correlated with help-seeking (r = −.52, p < .001). SEM results indicated that the structural model had good fit (CFI = 0.97, RMSEA = 0.048, TLI = 0.96), with shame significantly mediating the relationship between social desirability and help-seeking. Both direct and indirect effects of social desirability on help-seeking were statistically significant.Conclusion: The findings highlight that shame plays a critical mediating role in the negative relationship between social desirability and help-seeking behavior. Interventions aimed at reducing internalized shame and addressing socially desirable responding may be essential for improving help-seeking behaviors, especially in cultural contexts where stigma and social expectations are prominent.